Rastreamento do câncer de esôfago pela endoscopia digestiva transnasal e cromoendoscopia em pacientes com carcinoma de células escamosas de cabeça e pescoço - Vitor Nunes Arantes (2011)
Introduction: Esophageal cancer is usually detected at an advanced stage precluding curative treatment. Alcohol and tobacco abuse and head and neck cancer are factors associated with the development of squamous-cell carcinoma of the esophagus. Transnasal endoscopy (TNE) is routinely practiced in Japan and in European centers. The main advantage is that no sedation is required and therefore patient recovery is faster and costs are lower. In Latin-American countries, TNE is seldom practiced and there is not enough evidence about its suitability to these populations. Objectives: (1) to assess the clinical effectiveness of using TNE with white-light, FICE and lugol staining in patients with history of head and neck squamous-cell cancer to screen for esophageal cancer; (2) to assess the feasibility and the acceptance of Brazilian patients to undergo unsedated TNE; (3) to determine the prevalence of esophageal neoplastic lesions in our population; (4) to compare the performance of white-light endoscopy and FICE for esophageal cancer detection. Methods: Cross-sectional study. Inclusion criteria: patients with current or past history of head and neck squamous-cell cancer referred to esophageal cancer screening that agreed to participate in the study. Exclusion criteria: distant metastasis, nasal surgery, coagulopathy, iodine allergy, severe esophagitis and esophagectomy. Preparation: nasal application of vasoconstrictors and lydocaine. Procedures were performed without sedation with an ultra-thin endoscope (EG-530N, Fujinon Fujifilm Co., Japan). Patient tolerance was registered by the attending endoscopists. An independent observer interrogated the patient afterwards about pain or discomfort applying a validated visual analogic pain scale (VAS). Esophageal examination was randomly allocated to start with white-light by first operator, followed by digital chromoendoscopy (FICE) by second operator (blinded to the first procedure), followed by 0.8% lugol chromoscopy with the participation of both examiners. Performance of white-light examination and FICE for the detection of esophageal neoplasia was compared to the reference standard based on the identification of unstained areas larger than 5 mm, with the pink color sign and confirmatory histology. Adverse reactions were documented. Results: From May 2009 through April 2011, 106 patients were included in the study, 81% males, mean age 61 years-old (range: 31 to 89). TNE was feasible in 105 patients (99.1%) and mean exam duration was 17 min (range: 10 37 min). Patient tolerance was rated by the attending endoscopists as excellent in 83% of the subjects, good in 14%, fair in 1% and poor in 2%. Examination discomfort according to VAS was rated by 52% of the patients as absent, minimal by 40%, moderate by 4.6%, and intense by 1.9%. A total of 13 esophageal neoplastic lesions were detected (12.3%), with 10 early cancers. There was no difference among white-light endoscopy (sensitivity 92.3%, specificity 98.9%, accuracy - 98.1%) and FICE (sensitivity 100 %, specificity 98.9%, accuracy - 99%) for neoplasia detection. There was no serious complication related to the procedures. Conclusions: Unsedated TNE is feasible, well-accepted, safe and an efficient diagnostic tool for the screening of esophageal neoplasia in Brazilian high-risk patients. The rate of esophageal neoplasia in this population is high, which reinforce the recommendations to screen this population. The yield of white-light endoscopy and FICE are similar for esophageal neoplasia detection, and the combination of both techniques may potentially replace the use of lugol chromoscopy.